Creating Student Loyalty Through Reputation of Higher Education: An Empirical Study of Polytechnic in Bandung - Sugiharto, Nur Aziz; Hurriyati, Ratih; Gaffar, Vanessa (Fakultas Pendidikan Ekonomi dan Bisnis, 2021)
Abstract. This study aims to determine whether the loyalty of Polytechnic students can be formed through the reputation of Higher Education. Because student loyalty has an important role in realizing the competitive advantage of Higher Education. This research was conducted with a quantitative approach and data obtained through surveys using an online questionnaire with a sample of 200 Polytechnic students in the city of Bandung. Measurement of data and relationships between variables is done by using SEM-PLS statistical tools. The results show that student loyalty can be built through the reputation of higher education institutions with student satisfaction as interventing variable and various variables as forming the reputation of higher educationKey words. student loyalty; reputation; higher education; student satisfaction